BIBLIOMETRIC ANALYSIS TREND CUPPING THERAPY TREATMENT INTERVENTIONS FOR HEALTH - Yuri Santoso, May Dwi; Pranata, Satriya; Soesanto, Edy (International Journal of Islamic and Complementary Medicine, 2025)
Cupping therapy is a complementary medical intervention for health that has been around for thousands of years. This research provides information about trends in future research topics related to cupping therapy treatment interventions for health regarding low back pain, reducing pain and migraine. Data analysis in this research uses bibliometrics. Search for used data on the Web via http://app.dimensions.ai. Journals or data have more than 142 million articles and are limited from 2020-2024, by filtering data based on app.dimensions.ai which focuses on the fields of health sciences, nursing, clinical sciences, public health and the types of articles in publications. The data was analyzed into a bibliometric map using VOSviewer. As a result of data identification via app.dimensions.ai, there were 20,566 recorded data, by sorting based on the type of article and type of document, the results found were 2,062 articles. The highest number of publications on trends in cupping therapy treatment interventions for health regarding low back pain, reduce pain and migraine occurred in 2022 and the lowest occurred in 2021. Research on trends in cupping therapy treatment interventions for health regarding low back pain, reduce pain and migrancy was carried out not only in the health sector, medicine, nursing and psychology but also in other fields. The trending topic of cupping therapy treatment interventions for health is a topic that needs to be developed further as a complementary therapy for health. Suggestions for other researchers to choose topics that fall under low visualization to find research updates.